2019
DOI: 10.18671/scifor.v47n124.21
|View full text |Cite
|
Sign up to set email alerts
|

Influência de diferentes composições de lâminas de Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby e Pinus oocarpa var. oocarpa (Schiede ex Schltdl) para produção de compensados multilaminados

Abstract: Matos et al.-Influência de diferentes composições de lâminas de Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby e Pinus oocarpa var. oocarpa (Schiede ex Schltdl) para produção de compensados multilaminados adhesives and wood over MOE and MOR values obtained. Specifically for MOR values obtained through perpendicular static bending there was influence of adhesives utilized. Essays of glue line shear strength had demonstrated influence of layers structure, adhesive and interaction between layers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
1
2
5
Order By: Relevance
“…For ash contents, Matos et al (2019) obtained a content of 0.15% for Pinus wood, lower than that obtained in this study. Pereira et al (2014) obtained 0.68% for coffee wood.…”
Section: Basic Density Of Raw Materialscontrasting
confidence: 97%
See 1 more Smart Citation
“…For ash contents, Matos et al (2019) obtained a content of 0.15% for Pinus wood, lower than that obtained in this study. Pereira et al (2014) obtained 0.68% for coffee wood.…”
Section: Basic Density Of Raw Materialscontrasting
confidence: 97%
“…Based on the obtained value, pine wood can be classified as a low density wood (Figure 3), based on the classification by Coradin et al (2010) and Silveira, Rezende and Vale (2013), who stipulated values between 550 and 720 kg.m -3 for this class. The value obtaine d in this experiment was lower than the result obtained by Matos et al (2019), who reported 530kg.m -3 , for the same species at 18 years of age. is a natural and renewable organic compo u nd, which has properties that can contribute to the ad h esion process (Ang et al, 2019), it is noteworthy that its structure is similar to phenol-based adhesives (Qiao et al, 2015).…”
Section: Basic Density Of Raw Materialscontrasting
confidence: 78%
“…According to the literature, the total extractive values were close to those of Matos et al (2019) In general, the presented contents of the miriti residue do not present limitations, revealing a possible alternative material for manufacturing particleboards in terms of the chemical composition.…”
Section: Physical and Chemical Characterizations Of Pine And Miritisupporting
confidence: 69%
“…Este valor de teor de umidade permite a realização da colagem com adesivos utilizados na fabricação de compensados de paricá (Matos et al 2019). Por outro lado, considerando o teor de umidade obtido e a variação de umidade relativa do ar ao longo do ano na região de produção dos painéis de compensados analisados (Silva et al 2019), sobretudo durante a estação das chuvas, poderá fazer com que ocorram inchamentos e retrações significativas na madeira.…”
Section: Caracterização Físicaunclassified